PET/CT in Radiotherapy Planning - Chua, Sue (Springer International Publishing : Imprint: Springer, 2017)
This pocket book offers a succinct but comprehensive overview of the role of PET/CT in radiotherapy planning. Individual chapters are devoted to specific application of the technique to particular tumor types, including non-small cell lung, gastrointestinal, head and neck squamous cell, prostate, gynecological, and pediatric tumors. Helpful information is also presented on the practical implementation of PET/CT in routine oncological practice. Technical and logistical issues are discussed, and guidance provided on potential problems and pitfalls and available solutions. The book will be invaluable in assisting readers to exploit PET/CT's ability to significantly improve delineation of tumor tissue through the addition of metabolic information to structural imaging data, thereby avoiding unnecessary radiation injury and associated complications while enhancing therapeutic effects and minimizing the risk of marginal recurrences. It is published within the Springer series Clinicians' Guides to Radionuclide Hybrid Imaging, compiled under the auspices of the British Nuclear Medicine Society. .
Keywords: Medicine.; Nuclear medicine.; Radiotherapy.; elektronické knihy; electronic books